Peanut Mottle Virus (Ptmtv) Contamination on Peanut Seeds Collected from Several Locations and Its Elimination by Hot Water Treatment - Pudji Sulaksono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
The following observations on the seemingly prevalent occurrence of peanut (Arachis hypogaea) seed contaminations by PtMtV virus in the surrounding area of Palu, Central Sulawesi were conducted to determine the level of seed contamination and whether hot water treatment can be used to eliminate PtMtV virus from the seeds. Peanut seeds were collected from a number of locations and after soaking them in unheated water (29C) and heated water (55, 60 and 65C) for 10 minutes they were allowed to germinate, then transplanted and grown in pots in screen house. The effects of hot treatments on seed germinability, leaf formation, frequency of infection on surviving plants, and plant biomass production were determined. Seeds soaked in heated water showed different germinability, grew to become plants with different leaf formation and plant biomass production. Heat treatments gave different frequencies of infection on the plants. However, not a single heat treatment gave satisfactorily results in terms of giving zero or low infection and at the same time giving desirable seed germinability, leaf number, and plant biomass. The prospect of using hot water treatment at 55C or lower with longer soaking duration as a method for PtMtV virus elimination from peanut seeds is discussed.